2021
DOI: 10.1038/s41467-021-26991-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide signaling via its transformation to a stereospecific alkyl hydroperoxide that escapes reductive inactivation

Abstract: During systemic inflammation, indoleamine 2,3-dioxygenase 1 (IDO1) becomes expressed in endothelial cells where it uses hydrogen peroxide (H2O2) to oxidize L-tryptophan to the tricyclic hydroperoxide, cis-WOOH, that then relaxes arteries via oxidation of protein kinase G 1α. Here we show that arterial glutathione peroxidases and peroxiredoxins that rapidly eliminate H2O2, have little impact on relaxation of IDO1-expressing arteries, and that purified IDO1 forms cis-WOOH in the presence of peroxiredoxin 2. cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Because Prdx2 reduces most of the H 2 O 2 in human erythrocytes [ 23 , 65 , 71 ], H 2 O 2 influx rates in excess of ≈2 μM s −1 — corresponding to ≈80 nM plasma H 2 O 2 — should extensively oxidize this protein. However, Prdx2 is modestly oxidized in erythrocytes, even under lipopolysaccharide-induced endotoxemia, which strongly stimulates H 2 O 2 production by circulating phagocytes [ 72 , 73 ]. Therefore, H 2 O 2 in blood plasma does not reach the 100 nM range systemically.…”
Section: Discussionmentioning
confidence: 99%
“…Because Prdx2 reduces most of the H 2 O 2 in human erythrocytes [ 23 , 65 , 71 ], H 2 O 2 influx rates in excess of ≈2 μM s −1 — corresponding to ≈80 nM plasma H 2 O 2 — should extensively oxidize this protein. However, Prdx2 is modestly oxidized in erythrocytes, even under lipopolysaccharide-induced endotoxemia, which strongly stimulates H 2 O 2 production by circulating phagocytes [ 72 , 73 ]. Therefore, H 2 O 2 in blood plasma does not reach the 100 nM range systemically.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the active NADPH oxidase leads to an increase in oxygen consumption, which is referred to as “oxidative burst”. This creates superoxide anion radical ( ) in the lumen of the phagolysosome, which is converted into H 2 O 2 by superoxide dismutase (SOD) [ 59 ]. Further reactions lead to the formation of toxic ROS, including and from H 2 O 2 .…”
Section: Generation Of Ros/rnsmentioning
confidence: 99%
“…We expressed and purified the HsPrx2 and used the heterologous Trx system from S. cerevisiae (ScTrx1 and ScTrxR1) (S7E-S7G Fig) to perform the peroxidase activity assays by NADPH oxidation assay, as described previously by Truzzi and coworkers [35]. The need for the heterologous yeast system lies in the fact that human TrxR is a seleno protein able to decompose hydroperoxides [47,48], and the use of the human Trx system would make the results unreliable. The NADPH oxidation assay was performed using the same experimental conditions applied to the Prx bacterial isoforms, and the results revealed that compound C2 was not able to inhibit the human isoform HsPrx efficiently, since only a very slight decrease in peroxidase activity was detected (Fig 5A , Table 3).…”
Section: Plos Onementioning
confidence: 99%